Case Report: Fruquintinib-induced hyperbilirubinemia: a rare cause of dialyzer filter discoloration in a patient undergoing long-term dialysis - Galloway, Mercedes; Awad, Alaa S.; Heilig, Charles W. (Frontiers in Nephrology, 2025)
We report a case of a 55-year-old male patient with a medical history of cardiorenal syndrome and rectosigmoid colon adenocarcinoma, who started dialysis five years prior to presenting with unusual yellow discoloration of his dialyzer filter during his regular dialysis session. Following a regimen of standard chemotherapy, the patient was initiated on fruquintinib, 5 mg daily for 21 days, as an alternative treatment due to the intolerability of previous agents and failure of malignancy to respond. Shortly after starting fruquintinib, the patient developed hyperbilirubinemia and experienced significant yellow discoloration of the dialysis filter—a phenomenon not previously documented in association with this medication. The absence of dialyzer discoloration during five years of dialysis highlights the temporal relationship between the introduction of fruquintinib and the onset of filter discoloration. [removed some sentence] This case highlights the need for heightened awareness of potential adverse effects of fruquintinib, potentially detectable in patients undergoing dialysis, and aims to contribute to the growing body of literature on the medication’s safety profile.